Knee pain and its influence on quality of life and physical function in Jazan adult population: A cross sectional study - Zenat Khired; Fatimah Albeladi; Manal Abudeyah; Maryam Alluli; Abdullah Al Faqih; Abdullatif Suwaydi; Sarah Salih (Elsevier, 2023)
Background: Knee pain is primarily caused by knee osteoarthritis (OA). As a result, the quality of life and physical function of patients are affected. This study aimed to evaluate prevalence of knee pain and its influence on quality of life and physical function in the adult population of Jazan region of Saudi Arabia. Methods: A cross-sectional study among 480 above 40 years adults who had knee pain and diagnosed with knee OA was conducted. A questionnaire containing the Arabic validated versions of the International Knee Documentation Committee Subjective Knee Evaluation Form (IKDC) and the health-related quality of life (FS-12) was used. Data analysis included descriptive statistics, correlation and regression analysis. Results: IKDC mean score was 40.05 with SD 9.75. Pain was present in 77.8%; 12.4% indicated continuous pain and 6.5% indicated worst pain intensity. Physical function was normal in 14%, 48% could perform light activities without pain, and 11% are unable to perform any activity. Results show a statistically significant relationship between pain intensity and sex, age, and BMI and, between age and knee function. Regression analysis showed significant association with sex and age. Pain is four times more common in females. Mean HRQoL score was 39.46 with subscale: MCS (39.41) and PCS (39.50) scores. Conclusions: Low IKDC scores were reported among the adult population with OA. The majority suffered from pain in different degrees and intensities. Physical function was also impaired and the quality of life is affected. Better pain management is recommended for OA patients.